Sector level analysis: Impact of environmental, social, and governance performance on financial performance, stock performance, and firm value in Asia pre-and during the pandemic - Piamonte, Clarissa M. (Animo Repository, 2023)
ESG factors have been gaining attention in recent years as they provide a comprehensive view of a company's sustainability and ethical practices. The COVID-19 pandemic has also highlighted the importance of ESG factors, as companies that prioritize them may be more resilient and better equipped to handle crises. The objectives of this study are to determine the impact of Environmental, Social, and Governance performance on Financial performance, Stock performance, and Firm value among selected sectors in Asia, both pre-and during the pandemic. Using Refinitiv Eikon as the database, the sample used in the study consisted of 1,331 publicly-listed companies in Asia, classified into the following sectors: Basic Materials, Consumer Cyclicals, Energy, Financials, Industrials, Real Estate, and Utilities. An unbalanced panel data analysis was conducted to analyze the impact between the independent and dependent variables for 2017-2022. The research found that ESG score positively impacts Financial performance for Basic Materials pre-and during pandemic. Moreso, for the Financials sector, pre-and during pandemic, ESG score positively impacts Stock performance. The study also found ESG score to significantly negatively impact Tobin’s Q pre-and during pandemic for the Industrials sector. While for Consumer Cyclicals, the ESG score positively impacts Firm value during the pandemic only. Similar with the combined ESG score, the individual pillars concluded varying impacts among different sectors depending on the performance measured. However, the study found that for the Energy sector, the Financial performance, Stock returns, and Firm value are insignificant to ESG scores combined and individually. The results indicate that the importance and focus of ESG vary per sector.